Financial reform in the Philippines - Chua, Hwee Kian (2015)
It is widely acknowledged that developing a sound financial system is a pre-requisite for any economic development. The Philippines, being no exception, had for the past decade allowed market forces to determine interest rates, allocation of credit and the level of financial intermediation so as to improve the efficiency and stability of the financial system. In the early 1960s and 70s, the ceiling placed on interest rates badly distorted the intermediation process and discouraged banks to mobilise savings from the public. The several inefficiencies that existed in the financial sector clearly suggested the need for financial reforms in the 1980s. Hence, the main objective of their reforms is to improve the mobilization of funds, allocation of credit and enhance the effectiveness of the monetary policy. Experiences from other countries which underwent similar reform as the Philippines indicated that financial liberalization is no easy task. Reform is usually accompanied by adjustment problems with varying degree of seriousness. Therefore, it is of great importance that the relevant authorities or in this case, the Central Bank of the Philippines should exercise sufficient control over such policies so as to prevent undesirable developments in the financial system and ensuring that the policy objectives are duly met. Despite the fact that the Philippines is stepping into its fourth decade of financial reform, further deregulation measures are still expected to be announced in the future to consolidate its achievements to date and solve any problems that have arisen. As the reforms in the financial sector is expected to spark off growth in other areas like trade and investments, the future well-being of the Philippine economy lies greatly on the success of these reforms.